2019
DOI: 10.1111/jgs.16046
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Community‐Dwelling Status Among Survivors of High‐Acuity Emergency General Surgery Disease

Abstract: OBJECTIVES To examine loss of community‐dwelling status 9 months after hospitalization for high‐acuity emergency general surgery (HA‐EGS) disease among older Americans. DESIGN Retrospective analysis of claims data. SETTING US communities with Medicare beneficiaries. PARTICIPANTS Medicare beneficiaries age 65 years or older hospitalized urgently/emergently between January 1, 2015, and March 31, 2015, with a principal diagnosis representing potential life or organ threat (necrotizing soft tissue infections, hern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“… 16 As a large proportion of EL patients are elderly, postoperative geriatric assessment and care should receive more attention, in a manner analogous to orthogeriatric care in patients with hip fractures. 17 In the first 4 years that NELA data were collected, improvements in 30‐ and 90‐day mortality were most apparent in the oldest cohort of NELA patients. 18 On the same note, introduction of the ELAP pathway was associated with reduction in 30‐day mortality in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 As a large proportion of EL patients are elderly, postoperative geriatric assessment and care should receive more attention, in a manner analogous to orthogeriatric care in patients with hip fractures. 17 In the first 4 years that NELA data were collected, improvements in 30‐ and 90‐day mortality were most apparent in the oldest cohort of NELA patients. 18 On the same note, introduction of the ELAP pathway was associated with reduction in 30‐day mortality in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients are more likely to have age‐related physiological impairment and exhibit frailty, sarcopenia, and functional and cognitive impairment 16 . As a large proportion of EL patients are elderly, postoperative geriatric assessment and care should receive more attention, in a manner analogous to orthogeriatric care in patients with hip fractures 17 . In the first 4 years that NELA data were collected, improvements in 30‐ and 90‐day mortality were most apparent in the oldest cohort of NELA patients 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other studies evaluating predictive factors for patients diagnosed with an EGS condition undergoing surgical intervention, our study found that as age increased, so did the likelihood for being discharged to a facility for supplementary care. 10 An additional factor indicating likelihood that a facility would be needed at time of discharge was having more than two comorbidities before admission. As mentioned previously, as age increases, the likelihood for comorbidities being present also increases.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the rarity of this disease, approximately 2% incidence in one study, and the significant impact NSTIs cause on quality of life, a study assessing only this patient population is warranted, as very little has been reported in older adults. 10 NSTIs are rapidly progressing, life-threatening diseases, characterized by both inflammation and necrosis of subcutaneous fat, fascia, or muscle. 11 Despite advances in surgical and anti-infective therapy, NSTIs continue to have a significant mortality rate, with some studies reporting ranges from 24 to 34%.…”
Section: Introductionmentioning
confidence: 99%
“…In the year after surgery, older adults have a 30% 1-year mortality and high rates of healthcare utilization, suggesting that even patients who survive the initial hospitalization are extremely vulnerable. Among those who survive, one in 10 older Americans who were community-dwelling transfer to a nursing facility or long-term acute care facility by nine months postoperatively ( 42 ). Again, the “surprise question” is a simple and useful tool to screen patients for palliative care needs to identify patients with a high risk of death.…”
Section: Narrative Review Of Palliative Care Themesmentioning
confidence: 99%